A three‐dimensional atlas of the honeybee central complex, associated neuropils and peptidergic layers of the central body. Issue 14 (20th May 2022) - Kaiser, Andreas; Hensgen, Ronja; Tschirner, Katja; Beetz, Evelyn; Wüstenberg, Hauke; Pfaff, Marcel; Mota, Theo; Pfeiffer, Keram
Abstract: The central complex (CX) in the brain of insects is a highly conserved group of midline‐spanning neuropils consisting of the upper and lower division of the central body, the protocerebral bridge, and the paired noduli. These neuropils are the substrate for a number of behaviors, most prominently goal‐oriented locomotion. Honeybees have been a model organism for sky‐compass orientation for more than 70 years, but there is still very limited knowledge about the structure and function of their CX. To advance and facilitate research on this brain area, we created a high‐resolution three‐dimensional atlas of the honeybee's CX and associated neuropils, including the posterior optic tubercles, the bulbs, and the anterior optic tubercles. To this end, we developed a modified version of the iterative shape averaging technique, which allowed us to achieve high volumetric accuracy of the neuropil models. For a finer definition of spatial locations within the central body, we defined layers based on immunostaining against the neuropeptides locustatachykinin, FMRFamide, gastrin/cholecystokinin, and allatostatin and included them into the atlas by elastic registration. Our honeybee CX atlas provides a platform for future neuroanatomical work. Abstract : The central complex in the brain of insects is a highly conserved group of midline‐spanning neuropils that houses the internal compass. It is responsible for goal‐directed locomotion and involved in the regulation of sleep‐wake cycles. Honeybees have been a model organism for sky‐compass orientation for more than 70 years, but there is still very limited knowledge about the structure and function of their central complex. We created a high‐resolution three‐dimensional atlas of the honeybee central complex and associated neuropils, which includes layers defined by the distribution of neuropeptidergic immunoreactivity. Our atlas provides a platform for future neuroanatomical work into the central complex of the honeybee.